Adsorption of copper (II) ions from aqueous solution using bottom ash of expired drugs incineration - Thouria Benzaoui; Ammar Selatnia; Djaafar Djabali (Adsorption Science & Technology)
The use of bottom ash of expired drugs incineration for removal of Cu(II) ions from aqueous solution has been investigated. Analytical techniques have been employed to find characteristics of adsorbent materials. The removal of Cu(II) was conducted in batch system, and the effects of pH, adsorbent dosage, initial concentrations of copper ions, and contact time on adsorption efficiency were studied. Optimum adsorption was achieved at a pH 5 and equilibrium was established within 15 min of the process. The equilibrium adsorption data were analyzed using eight adsorption isotherm models: Langmuir, Freundlich, Temkin, Redlich–Peterson, Dubinin–Radushkevich, Toth, Harkin–Jura and Halsey isotherms. The energy value obtained by application of Dubinin–Radushkevich model was 2.593 kJ/mol indicating that physisorption was the dominant mechanism of sorption. The values of the correlation coefficient (R 2 ) of the isotherms gave the best fit (>0.99) with the Langmuir, Toth, and Redlich–Peterson isotherms. The adsorption capacity (q m ) from the Langmuir isotherm for Cu(II) was found as 13.335 mg/g. The equation constant n of Toth isotherm model is found to be close to 1 (0.945), confirming that the adsorbent studied presents homogeneous surface under conditions used. It is concluded that bottom ash of expired drugs incineration can be used as an effective adsorbent for removing Cu(II) from aqueous solution.